UPAYA DIPLOMASI PUBLIK KOREA SELATAN DALAM MEMPROMOSIKAN BUDAYA DAN PARIWISATA DI INDONESIA MELALUI PROGRAM “TEKO NANG JAWA” 2019 - Cristin Fariani; Putri Hergianasari; Triesanto Romulo Simanjuntak (Cakrawala Jurnal Penelitian Sosial, 2019)
South Korea is one of the countries in East Asia that adopts a foreign policy approach through non-state actors. This approach is also known as a public diplomacy. This study aims to explain about a program named Teko Nang Jawa 2019. Teko Nang Jawa 2019 is a public diplomacy program which held in Indonesia by South Korea government. This program aims to promote South Korea’s culture and cultural tourism in Indonesia. The explanation begins with the South Korea nation branding, culture, and cultural tourism progress. This research used qualitative research method with descriptive explanation about the detail of the program. The data were analyzed through literature study and interview. The researcher found that there are many actors participate in this pubic diplomacy program. Korean wave, which is South Korea nation branding, is an instrument in public diplomacy. Teko Nang Jawa 2019 program was held to promote culture and cultural tourism intensely to the Indonesian especially in java. Public diplomacy done by the South Korea government to achieve the national interest such as national security, economic development, increase national power and national prestige interest.